SAT0694 Subgrouping of early ra-patients identified cluster of patients with high levels of pain, fatigue and psychosocial distress 3 years after diagnosis. (15th June 2017) - Lindqvist, J; Westerlind, H; Klareskog, L; Alfredsson, L; Lampa, J
Abstract : Background: The wide range of effective treatment alternatives for rheumatoid arthritis (RA) makes treating the disease to inflammatory remission a feasible goal for a majority of patients. However, earlier studies have reported that symptoms other than inflammatory disease activity causes a substantial burden of illness for RA-patients. These unmet needs include persistent pain, fatigue, impaired physical function and mental health status (1). Objectives: To identify clusters of early RA-patients based on pain, fatigue, sleep, physical function, mental health status and perceptions of quality of life, 3 years after diagnosis. Withal investigate associations between clusters and clinical parameters at the time of diagnosis. Methods: Data was compiled from the Swedish case-control cohort Epidemiological Investigation of Rheumatoid Arthritis (EIRA) and linked to the Swedish Rheumatology Quality Register (SRQ). All patients were diagnosed with RA according to the 1987 ACR criteria. Early RA-patients with clinical data from diagnosis and 3 year follow-up questionnaire data were included (N=618; 74% women, median age at diagnosis 58 years). Measurements of pain, fatigue, sleep problems, physical and mental functioning and quality of life was entered into a hierarchical agglomerative clustering procedure using Ward's method of squared Euclidian distances. Number of clusters was determined by largest changes in distances at which clusters were formed. Associations between clusters and clinical variables at diagnosis were calculated using contingency analysis. All statistical analysis was performed using jmp statistical software (SAS, US). p<0.05 was considered significant. Results: The cluster analysis identified three distinct clusters. Cluster 1 consisted of 178 patients (29%) doing significantly worse for all included variables. Cluster 3 consisted of 209 patients (34%) doing very well and cluster 2, consisting of 231 patients (37%), constituted an intermediate group doing fairly well. Cluster 1 was associated with female sex (p=0.0007) and lower education level (p=0.0003) compared to cluster 3. Cluster 1 was also associated to higher HAQ (p<0, 0001), higher patient global assessment of health (p<0.0001), higher pain ratings (p<0.0001) and lower swollen/tender joint count ratio (STR) (p=0.0065) at the time of diagnosis compared to cluster 3. Conclusions: Through cluster analysis, we could identify a subgroup of almost a third of the RA-patients with high levels of pain, fatigue, sleep problems and poor physical and mental health related quality of life 3 years after RA-diagnosis. These symptoms are indicative of a central sensitization syndrome and these findings indicate that other factors than inflammatory disease activity causes a significant burden of illness also at an early stage of RA and that there is a need of additional intervention strategies for these patients. References: Taylor PC, Moore A, Vasilescu R, Alvir J, Tarallo M. A structured literature review of the burden of illness and unmet needs in patients with rheumatoid arthritis: a current perspective. Rheumatol Int. 2016;36(5):685–95. Acknowledgements: All patients and staff involved in EIRA ans SRQ. Disclosure of Interest: None declared